Eksistensi BUMG Terhadap Tingkat Kesejahteraan Masyarakat di Gampong Suak Sigadeng Kecamatan Johan Pahlawan Kabupaten Aceh Barat - Alisman; R. Abdul Khalid Munandar; Chairul Amni; Mira Chairani; Zahara (Jurnal EMT KITA, 2023)
BUMG is a business entity intended for the welfare of the community. If BUMG management is carried out well, it will be very beneficial for all people, but if it cannot be managed properly, it will not have an impact on the welfare of the community. Therefore, researchers are interested in researching and studying more deeply about this. To obtain data, the data collection techniques that the authors use are in two ways, namely library research and field research consisting of observations, interviews, and questionnaires. The research method that the author uses is a qualitative method using alternative answers on a Likert scale. The population in this study were all the people of Gampong Suak Sigadeng, West Aceh District. And the sample is 100 people. Based on the results of the research that the researchers have done, it can be concluded that the existence of BUMG influences the welfare of the community in Gampong Suak Sigadeng, Johan Pahlawan District, West Aceh Regency. respondents who answered strongly disagree and disagree (S+SS > STS+TS) with an average percentage of 78.36% > 4.12%. Thus, the hypothesis is accepted.